ans. this guys...#brainly users.....
Attachments:
![](https://hi-static.z-dn.net/files/d2c/44f21005b1faecabbcbf21295a61ef55.jpg)
Answers
Answered by
27
Given
→ cos∅ + cos²∅ = 1
→ cos∅ + 1 - sin²∅ = 1
One cancels out both sides,
→ cos∅ = sin²∅
Solution
Hence Proved
BrainlyRacer:
Great Bossssss!!!!!!!!!
Answered by
10
Answer:
: Solution :
=sin^12∅ + 3sin∅ + 3sin^8∅ + sin^6∅+ 2sin^4∅ + 2 sin^2∅ - 2.
=(sin^4∅)^3 + 3(sin ^4∅)^2 sin^2∅ + 3sin ^4∅ ( sin ^2∅)^2 + (sin^2∅ )^3 + 2(sin^2∅ )^2 + sin^2∅ ) - 2 .
= (sin^4∅ + sin^2∅ )^3 + 2(cos^2∅ + cos∅) -2
= (cos^2∅ + cos∅)^3 + 2(1) - 2
= 1 + 2 - 2
= 1
= So it is proved .
Similar questions
Social Sciences,
7 months ago
Environmental Sciences,
7 months ago
Social Sciences,
7 months ago
Political Science,
1 year ago
Biology,
1 year ago
Math,
1 year ago